Fish presence and inter‐patch connectivity interactively alter the size of emergent insects in experimental enclosures. Issue 3 (5th March 2018) - Pitcher, Kristopher A.; Soluk, Daniel A.
Abstract: Structural habitat complexity (SHC) and functional habitat connectivity (FHC) are the basic components that make up the physical architecture of an ecosystem, and can have substantial impacts on predator–prey interactions. These structural components influence animal behaviors such as inter‐patch movement, foraging, and competition, and can impact community structure/dynamics in terrestrial and aquatic ecosystems. The effects of SHC and FHC on predator–prey dynamics within an ecosystem may also have important cascading effects on neighboring ecosystems by altering the movement of individuals across ecosystem boundaries. For example, when aquatic insects emerge as adults, they enter terrestrial ecosystems where they become an important food resource for terrestrial predators. Using a multiple patch, predator enclosure design in ponds, we tested whether altering intra‐patch plant stem densities (SHC) and inter‐patch distances (FHC) would influence the impact a predatory fish has on the biomass, quality, and trophic composition of emergent insects. As expected, fish significantly reduced emergent insect biomass (33% ± 7.6, mean ± SE). Intra‐patch stem densities (SHC) did not significantly alter fish effects; however, inter‐patch distance (FHC) did significantly alter the impact of fish on the size of some emergent insects. Damselflies that emerged in treatments with fish present and shorter inter‐patch distances were significantly larger, 4.1 ± 0.1 mg/m 2 compared to 3.3 mg/m 2 ± 0.1 in the long/fish treatments. In fish treatments, this effect on damselfly size resulted in greater reductions in total emergent insect biomass in long inter‐patch distance treatments (47.3% ± 6.9) compared to short inter‐patch distance treatments (20.5% ± 12.4). Our results suggest that physical components of a habitat, such as inter‐patch distances, have important impacts on predator–prey dynamics within habitats. These altered predator–prey dynamics can then have cascading effects on adjacent habitats by influencing the abundance, trophic composition, and quality of exported trophic subsidies.